Coordinating signs and eye gaze in the depiction of directions and spatial scenes by fluent and L2 signers of Norwegian Sign Language. Issue 3 (3rd July 2019) - Ferrara, Lindsay
ABSTRACT: The current study investigates the coordination of signs and eye gaze during depictions of directions and spatial scenes by fluent and second language (L2) signers of Norwegian Sign Language. First, findings show that fluent and L2 signers make different choices regarding the perspective they use to depict spatial scenes. Second, there is variation within and across groups in relation to how eye gaze is directed during these depictions. Findings suggest that eye gaze is used to establish a vantage point upon a depicted scene, but L2 learners may not always engage in this type of coordination. This study contributes to our understanding of how visual perspective is depicted in signed languages and has implications for signed language pedagogy.